MANAGEMENT AUDIT OF THE HUMAN RESOURCES FUNCTION AT PT POS INDONESIA (PERSERO) KCU SEMARANG - Pranala Mahanani Raharjo; Rudi Handoyono; Alvianita Gunawan Putri (Politeknik Negeri Semarang, 2023)
This study aims to analyze the effectiveness of 8 (eight) HR functions at PT Pos Indonesia (Persero) KCU Semarang. This research is a qualitative study, through the distribution of questionnaires using a purposive sampling technique. Data collection techniques were carried out by interviews, questionnaires, documentation studies, and observations. Data analysis uses management audit with four stages, namely preliminary audit, management control reviews and tests, detailed audits, and reports. The results show that the company has implemented 8 (eight) existing HR functions. In the implementation of the 8 (eight) HR functions, it was found that performance appraisal, reward and compensation system, employment relations, and termination of employment function have been effective. The functions of orientation and placement, training and development.